The Analysis of Wind Farm Impact in Primary Radar System - Pidanič, Jan; Juryca, Karel; Suhartanto, Heru (University of Indonesia, 2017)
The paper deals with problematic of the influence of the wind turbines on the Primary Radar System. A real scenario that includes two wind turbines was chosen for the analysis. A simulator of reflected signals from the wind turbines was developed. In the start of paper, the principle of the developed simulator is described followed by the own analysis. The results from the work will be used for developing of the mitigation techniques for suppression of this influence.
Analýza dopadu větrných elektráren na primární radarové systémy
Keywords: wind turbine; primary radar system; reflection, Radar Cross Section, wind farm, Doppler shift, RCS; větrná elektrárna; primární radarový systém; odrazy signálů; efektivní odrazná plocha; větrné farmy; Dopplerovský posun; RCS